Nano-engineering of electron correlation in oxide superlattices. Issue 3 (23rd October 2017) - Laverock, J; Gu, M; Jovic, V; Lu, J W; Wolf, S A; Qiao, R M; Yang, W; Smith, K E
Abstract: Oxide heterostructures and superlattices (SLs) have attracted a great deal of attention in recent years owing to the rich exotic properties encountered at their interfaces. We focus on the potential of tunable correlated oxides by investigating the spectral function of the prototypical correlated metal SrVO3, using soft x-ray absorption spectroscopy and resonant inelastic soft x-ray scattering to access both unoccupied and occupied electronic states, respectively. We demonstrate a remarkable level of tunability in the spectral function of SrVO3 by varying its thickness within the SrVO3 /SrTiO3 SL, showing that the effects of electron correlation can be tuned from dominating the energy spectrum in a strongly correlated Mott–Hubbard insulator, towards a correlated metal. We show that the effects of dimensionality on the correlated properties of SrVO3 are augmented by interlayer coupling, yielding a highly flexible correlated oxide that may be readily married with other oxide systems.